2004
DOI: 10.1186/1476-511x-3-15
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: IntroductionOxidative stress has been demonstrated in malaria. The potential oxidative modification of lipoproteins derived from malaria patients was studied. These oxidized lipids may have role in pathogenesis of malaria.MethodThe plasma lipid profile and existence of oxidized forms of very low density lipoprotein (VLDL), low density lipoprotein (LDL) and high density lipoprotein (HDL) were investigated in malaria (17 mild and 24 severe patients) and 37 control subjects. Thiobarbituric acid reactive substance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Additionally, it is likely that the parasite modifies metabolic pathways of lipids in the hepatocytes. Finally, oxidative stress has been associated with oxidation of lipoproteins, contributing to the abnormalities of lipids levels [17, 24, 26]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it is likely that the parasite modifies metabolic pathways of lipids in the hepatocytes. Finally, oxidative stress has been associated with oxidation of lipoproteins, contributing to the abnormalities of lipids levels [17, 24, 26]. …”
Section: Discussionmentioning
confidence: 99%
“…In fact, a high proportion of children with malaria present HDL and LDL levels below normal range. The mechanisms by which inflammation and infection decrease HDL levels are uncertain, but in acute malaria two factors contribute for these findings: the redox imbalance which favors the oxidation of lipoproteins; the mobilization of cholesterol internalized by lipoproteins by Plasmodium [17, 23, 26]. Additionally, the occurrence of functional alterations of these lipoproteins is likely, as seen in other inflammatory disorders, such as the diminished ability of HDL to prevent the oxidation of LDL [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we show here that hGIIA is inactive against P. falciparum at concentrations as high as 1.5 M under standard culture conditions, which suggests that its role in malaria, if any, might rather relate to inflammatory response of the host than direct inhibition of parasite development. However, it has been shown that hGIIA sPLA 2 exhibits enhanced potency toward HDL from acute-phase serum (56) and in vitro-oxidized lipoproteins (57), which raises the possibility that this sPLA 2 might be active against Plasmodium under pathophysiological conditions when lipoproteins get oxidized (58).…”
Section: Figmentioning
confidence: 99%
“…Measurements of resonance energy transfer from tryptophan of the LDL particles to pyrene and pyrene monomer-excimer formation was used to determine the annular and bulk fluidity respectively (Avdulov et al, 1997; Hashimoto et al, 2001; Sibmooh et al, 2004). Briefly, 10 mM PBS (pH 7.4) was added to the LDL samples to make a final volume of 2 mL containing 50 μg/ml protein.…”
Section: Methodsmentioning
confidence: 99%